Association of coffee, green tea, and caffeine with the risk of dementia in older Japanese people. Issue 12 (8th October 2021) - Matsushita, Nana; Nakanishi, Yuta; Watanabe, Yumi; Kitamura, Kaori; Kabasawa, Keiko; Takahashi, Akemi; Saito, Toshiko; Kobayashi, Ryosaku; Takachi, Ribeka; Oshiki, Rieko; Tsugane, Shoichiro; Iki, Masayuki; et al.
Abstract: Objectives: Coffee, green tea, and caffeine are potential preventive factors for dementia, but the underlying evidence is insufficient. This study aimed to examine associations between the consumption of coffee, green tea, and caffeine and dementia risk in middle‐aged and older people. Methods: This was a cohort study with an 8.0‐year follow‐up. Participants were community‐dwelling individuals ( n = 13, 757) aged 40–74 years. A self‐administered questionnaire survey was conducted in 2011–2013. Predictors were the consumption of coffee/green tea, from which caffeine consumption was estimated. The outcome was incident dementia obtained from the long‐term care insurance database. Covariates were demographic factors, body mass index, physical activity, energy, smoking, drinking, and disease history. Adjusted hazard ratios (HRs) were calculated using Cox proportional hazards models. HRs were also calculated using a Cox model with delayed entry. Results: The number of dementia cases during the study period was 309. Participants with higher coffee consumption had lower HRs (adjusted p for trend = 0.0014), with the fifth quintile (≥326 ml/day) having a significantly lower HR (0.49, 95% confidence interval [CI]: 0.30–0.79) than the first quintile (<26 ml/day, reference). Similarly, participants with higher caffeine consumption had a significantly lower HR (adjusted p for trend = 0.0004) than the reference. The Cox model with delayed entry yielded similar results. These associations were significant in men, but not in women. Moreover, participants who consumed 2–2.9 cups/day and ≥3 cups/day of coffee had lower HRs (0.69, 95% CI: 0.48–0.98 and 0.53, 95% CI: 0.31–0.89, respectively) than those who consumed 0 cup/day. The association between green tea consumption and reduced dementia risk was significant (adjusted p for trend = 0.0146) only in the 60–69 years age subgroup. Conclusions: High levels of coffee and caffeine consumption were significantly associated with a reduced dementia risk in a dose‐dependent manner, especially in men. Moreover, coffee consumption of ≥3 cups/day was associated with a 50% reduction in dementia risk.